Case Report: Exploring the clinical spectrum of LGMD R27: insights from a case study with homozygous pathogenic variant in the JAG2 gene - Nikitin, Sergey; Melnik, Evgeniya; Sharkova, Inna; Murtazina, Aysylu; Shchagina, Olga; Zabnenkova, Victoriia; Tsargush, Vadim; Dadali, Elena; Kutsev, Sergey (Frontiers in Pediatrics, 2024)
Limb-girdle muscular dystrophies (LGMD) constitute a heterogeneous group of genetic disorders characterized by progressive muscle weakness and atrophy, predominantly affecting the muscles of the pelvic and shoulder girdles. LGMD R27, linked to biallelic pathogenic variants in the JAG2 gene, was recently described, and to date, only 27 cases has been published in three reports. Here, we present two siblings exhibiting a severe clinical phenotype of LGMD R27, associated with a novel JAG2 homozygous frameshift variant (c.3467_3470dup, p.(Pro1158AlafsTer22)) results in truncated protein with 21 amino acid substitution within the cytoplasmic domain of the Jagged2 protein.